Legal Protection For Occupants Of Magersari Land Held For 90 Years - Farah Fauziah Maulana; Rahayu Subekti; Isharyanto Isharyanto (IHSA Institute, 2025)
This study examines the form of legal protection for the community that has occupied Magersari land for approximately 90 years against illegal transfer of rights. Long-term occupation of land has given rise to certain rights for the occupants, but these rights are often threatened by illegal actions that have the potential to harm them. The approach of this study used normative juridical, examining the provisions of laws and regulations, legal doctrines, and relevant court decisions. Based on Article 24 paragraph (2) of PP No. 24 of 1997 concerning Land Regristration, individuals who have physically controlled land for more than two decades in good faith and without dispute can apply for registration of land rights. This provision is very relevant to the condition of Magersari land, where the community has occupied the land for generations and is recognized by the surrounding community. Evidence of physical control, reinforced by a letter of reference from the local village office, can be used as an administrative basis for the legalization process. The results of the study confirm that legal recognition through land registration is an important step in ensuring legal certainty, protecting community rights, and preventing future agrarian disputes.